Acute Phase Proteins Reaction in Ruminants - Jaipeng, Patipan; Sukasem, Leenawat (Journal of Mahanakorn Veterinary Medicine, 2018)
When body tissue injury is happened from various causes such as many pathogens and abnormal cells, inflammatory response is basic mechanism against those pathogens. In the first time of inflammatory reaction, acute phase response or acute phase reaction was stimulated in this time with secretion of substances at acute phase. Acute phase reaction is complicate process and many body cell coordinate in this reaction. Acute phase proteins change within a few hours after stimulation from pathogens, including various substances connecting with disease cause in several body systems of ruminants. This reaction represents to inflammatory response of body which quick response than hematological change. This review article aims to gather information about deviation of some protein amounts responding to acute phase reaction of inflammation in ruminants for further researches.